2007
DOI: 10.1093/annonc/mdl394
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between LAPTM4B gene polymorphism and susceptibility of gastric cancer

Abstract: This study indicated that allele *2 of LAPTM4B might be the risk factor of gastric cancer, which could be associated with genetic susceptibility of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Previous studies indicated that LAPTM4B polymorphism was associated with susceptibility to liver cancer, 26,33 gall bladder carcinoma 26 cervical carcinoma, 34 gastric cancer, 27 breast cancer, 24,25 colon cancer, 28 endometrial carcinoma, 20 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that LAPTM4B polymorphism was associated with susceptibility to liver cancer, 26,33 gall bladder carcinoma 26 cervical carcinoma, 34 gastric cancer, 27 breast cancer, 24,25 colon cancer, 28 endometrial carcinoma, 20 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14,[24][25][26][27][28][29][30][31] To the best of our knowledge, there is no report on the impact of LAPTM4B genotype on PCa. Therefore, in the present study we aimed to evaluate the possible association between LAPTM4B gene polymorphism and the risk of PCa in a sample of the Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…LAPTM4b is a candidate oncogene whose expression is increased in hepatocellular carcinoma, ovarian cancer and gastric cancer (Kasper et al, 2005;Liu et al, 2007;Yang et al, 2010). Furthermore, expression of LAPTM4b contributes to chemotherapy resistance in breast cancer by preventing transport of the anthracycline doxorubicin to the nucleus (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Allele *1 contains only one copy of a 19-bp sequence at the 5'UTR in the first exon, whereas the sequence in allele *2 is duplicated and tandemly repeated [14]. Previous study showed that LAPTM4B *2/2-type allele was significantly associated with the susceptibility of various adenocarcinoma including breast cancer [15][16][17], HCC [18,19], non-small lung cancer [20], gastric cancer [21], cervical cancer [22], colorectal cancer [23], lymphoma [24], gallbladder carcinoma [25], ovarian carcinoma [26] and malignant melanoma [27]. Therefore, we hypothesized that if there are some specific transcription factors binding to the LAPTM4B polymorphism region which play important roles in regulating LAPTM4B expression.…”
Section: Introductionmentioning
confidence: 99%